Evaluación de abonos foliares orgánicos en el cultivo de maní caramelo (Arachis hypogaea L.) en el recinto Francisco de Orellana, cantón Santo Domingo de los Tsáchilas - Nabas Sánchez, Carlos Javier (2016)
Research evaluation of organic foliar fertilizers in the cultivation of peanut candy (Arachis hypogaea L.) In the grounds Francisco de Orellana, Canton Santo DOMINGO main objective: to evaluate the effect of five treatments in organic foliar fertilizer crop yield of peanut (Arachis hypogaea L). Consequently for development in the methodology we used five treatments with four repetitions, using the complete block design at random (DBCA), statistical analysis it performed with InfoStat 2.0 program using the Tukey test at 95% confidence . The variables evaluated in this study were: flowering, plant height, number of pods per plant, grains per pod, quintals per hectare yield and economic analysis. The results obtained in this research were as follows: As regards the days to flowering began at 20 after sowing (days) with an average of 12%, to 31 (days) reached 87% flowering to all treatments and coming in full bloom at 35 days The variable plant height at harvest indicate that treatment T-3 obtained (53.18 cm) followed by the T-2 (46.70 cm) height less other treatments yielded an average height of 47-49 cm. In the number of pods per plant at harvest it was found that treatment T-1with (29.5) followed by T-5 (28.1) with fewer pods for other treatments. Regarding the number of grains per pod it is appreciated that the treatment Biofermento supermagro gives a number of 3.2 grains / sheaths, followed by the token T-5 (3.20), T-4 (3.13), the treatments and Te Biol manure obtained a mean of 3.10 grains / pod The highest yield obtained at the T-4 you fruit with 62 qq ha-1 and the lowest entry for the biological t ha-1 44 qq. Treatments that achieved the greatest economic benefit T-4 were you with fruit ($ 3,463.20), T-3 bioferemento supermagro ($ 3,182.20) and the lowest yield with T-1 biological ($ 2,315.11). We conclude that the variables evaluated in this research the best performance T-4 you fruit, T-3 supermagro biofermento, may be recommended to continue with assessments of this research to validate and transfer these results to the agro-ecological zone of the province Tsáchilas.